i Área Jurídica, Social y Administrativa CARRERA DE ADMINISTRACIÓN DE EMPRESAS TITULO: AUTOR: Henry Castillo Gonzaga DIRECTOR: Ing. Manuel Pasaca Mora LOJA-ECUADOR 2016 TESIS PREVIA A LA OBTENCIÓN DEL GRADO DE INGENIERO COMERCIAL. VALORACIÓN DE PUESTOS Y EVALUACIÓN DEL DESEMPEÑO DEL TALENTO HUMANO EN LA “COMERCIALIZADORA RAMIREZ GALVÁN – ZERIMAR” DE LA CIUDAD DE LOJA - Castillo Gonzaga, Henry (2016)
This research has the general objective MAKE A VALUATION OF POSITIONS AND A STUDY ON THE PERFORMANCE OF HUMAN TALENT THAT IS PART OF THE "COMERCIALIZADORA RAMIREZ GALVÁN CIA. LTDA. - ZERIMAR CITY OF LOJA "Moreover, the work allowed to know how important the job evaluation and performance evaluation of staff within the company. The following materials and methods that were based on the descriptive method were determined, helped analyze and describe the current reality of the trading, as regards development of human talent is concerned, among others; analytical method was used based on the diagnoses executed according to the specific objectives; inductive method helped to know the most important aspects of the Distributor; deductive method that I allow identifying characteristics contained in the general situation of the problem as it relates to techniques for managing human resources to develop this research. Also research techniques were used as direct observation, to identify activities to personnel management in order to know the problem; one surveys of the 45 workers where the results and formulating the proposal was based was made; also the interview technique was used, it held the manager of the company, to collect additional primary information. The procedure for the elaboration of the thesis after obtaining primary data and in contrast to the secondary information was as follows: Presentation of results, making the diagnosis. 6 Later this information the proposal will contribute to better management of human talent in this organization is formulated, this includes staff appraisal through her efficiency, effectiveness and relevance; as to the result of evaluating the performance of the company has thrown the performance indicator of 2.97 which means that the company is poised to strengthen as the average weighting factor is 2 and the case study a value larger than 2.97 was found. This result indicates an internal position in contrast to the development which is compatible with the rates of improvement in the results of the performance evaluation study of workers has produced the performance indicator of 3.02 which means that is a company strengthened, which should be capitalized to obtain a competitive advantage. Furthermore, the valuation of positions where the system was applied for points with their respective stages from defining factors to the recovery of jobs where the following results were obtained by total points is 5818 valuation was made, salaries paid to employees of the company amounted to an amount of $ 9,210.00 based on the aforementioned wage adjustment value by a factor of 1.58 valuation in order to determine the new wage was performed. The proposals are presented in order to improve the management of human resources in the company are: Proposal for Recruitment and Selection, Induction Proposal, Proposal Annual Training Plan and Proposed Plan of motivation and incentives for Workers "Zerimar" 7 Finally, with the information above conclusions and recommendations regarding Human Resource Management arise, bibliography and related annexes indicated.